2020
DOI: 10.1038/s41380-020-0756-y
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic and prefrontal GABA concentrations but not GABAA receptor densities are altered in high-functioning adults with autism spectrum disorder

Abstract: The gamma aminobutyric acid (GABA) neurotransmission system has been implicated in autism spectrum disorder (ASD). Molecular neuroimaging studies incorporating simultaneous acquisitions of GABA concentrations and GABA A receptor densities can identify objective molecular markers in ASD. We measured both total GABA A receptor densities by using [ 18 F]flumazenil positron emission tomography ([ 18 F]FMZ-PET) and GABA conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 58 publications
6
40
0
Order By: Relevance
“…Participants were of the same cohort that had been studied in a previous investigation by our lab 24 . We will refer to this cohort as the HFASD cohort.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were of the same cohort that had been studied in a previous investigation by our lab 24 . We will refer to this cohort as the HFASD cohort.…”
Section: Participantsmentioning
confidence: 99%
“…Sensorimotor processing may be related to aberrant inhibitory neurotransmission in ASD. Altered cortical inhibition is a widely supported theory in ASD, as evidenced by altered levels of glutamate 22 and GABA 23,24 , and sensory hyper-and hyposensitivity 1 . Neurodevelopmental disorders associated with ASD, such as fragile X Syndrome and Tourette syndrome, also exhibit alterations of cortical inhibition and suggest an involvement of sensorimotor deficits 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…1 H-magnetic resonance spectroscopy ( 1 H-MRS) is an MRI technique clinically used to study brain disease (Öz et al, 2014;Wilson et al, 2019), including the measurement of GABA in respect to autism spectrum disorder (Harada et al, 2011;Horder et al, 2018;Fung et al, 2020). 1 H-MRS is capable of non-invasively measuring neurotransmitters and metabolites, in vivo and is typically utilized in conjunction with structural MRI (sMRI) to assess neurochemical composition within brain anatomical regions (Faghihi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To date, clinical studies using 1 H-MRS to study GABA in ASD have found a decrease in GABA concentration in the frontal lobe of children with ASD (Harada et al, 2011) while, alternatively found an increase in the dorsal lateral prefrontal cortex in adults with ASD (Fung et al, 2020). PET imaging studies in participants with FXS have found a structurally-dependent decrease in GABA A receptor binding potential primarily for the thalamus (D'Hulst et al, 2015) using 11 C-Flumazenil (FMZ), a GABA A antagonist that binds to the post-synaptic benzodiazepine site of the GABA A receptor, between the α and γ subunits.…”
Section: Introductionmentioning
confidence: 99%
“…A collapse of GABAergic transmission leads to neuronal hyperexcitability and the subsequent development of epileptic seizures [ 3 , 4 ]. An aberrant GABAergic system is also associated with neurological disorders such as Alzheimer’s disease (AD), Parkinson’s disease (PD) and autism spectrum disorders (ASD) [ 5 , 6 , 7 ], often co-occurring with epileptic seizures [ 8 , 9 ]. Many anticonvulsants promote GABAergic neuronal transmission by enhancing the activity of the GABA type-A (GABA A ) receptor and increasing GABA content in the synaptic cleft [ 4 , 10 ].…”
Section: Introductionmentioning
confidence: 99%